David B. Audretsch: Clarivate Citation Laureate 2021 - Christina Guenther; Erik E. Lehmann (Small Business Economics, 2021)
Plain English Summary David B. Audretsch was named a 2021 Clarivate Citation Laureate, together with four other colleagues in the field of economics. A Clarivate Citation Laureate is recognized as having a research record and impact commensurate with that deemed to be 'of Nobel class.' This article briefly highlights the life and work of David B. Audretsch, Co-founder and Co-Editor in Chief of Small Business Economics: An Entrepreneurship Journal (SBEJ). Relying on bibliometric work published in the last years, this article briefly highlights the impact and influence of David B. Audretsch in the field of innovation and entrepreneurship.
Keywords: 330; Management; Microeconomics; Entrepreneurship; Industrial Organization